The Role of Physical Activity in the Prevention and Treatment of Depressive Disorders: Comprehensive Literature Review - Młynarczyk, Katarzyna; Buczek, Sylwia; Bury, Karolina; Byjoś, Ewa; Fabiś, Katarzyna; Mateja, Patrycja; Milewska, Kamila; Mstowska, Weronika; Naliuka, Hanna; Zbylut, Mateusz (Journal of Education, Health and Sport, 2026)
Background: Depressive disorders are among the leading contributors to global disability, affecting millions worldwide and imposing a major burden on public health systems. While pharmacotherapy and psychotherapy remain primary treatment modalities, physical activity (PA) has emerged as a promising strategy for both prevention and treatment of depression. Methods: This narrative review synthesizes evidence from high-quality meta-analyses, systematic reviews, prospective cohorts, randomized trials, and mechanistic research published between 2000 and 2025. Studies were selected based on relevance to PA’s preventive or therapeutic effects on depression and its underlying mechanisms. Results: Robust evidence indicates that higher levels of PA reduce the risk of incident depression by approximately 15–30% across populations [1–4]. Longitudinal studies demonstrate temporal and dose–response associations, fulfilling several Bradford Hill criteria. Exercise interventions produce moderate-to-large therapeutic effects in adults [5–7], significant improvements in adolescents and young adults [8], and additional benefits across perinatal, elderly, and medically comorbid groups [9–12]. Mechanistic research highlights neurobiological pathways, anti-inflammatory responses, autonomic improvements, enhanced cognitive function, and psychosocial resilience [13–18]. Conclusion: PA is a safe, feasible, and clinically meaningful intervention for preventing depressive disorders and improving outcomes among individuals with depression. Integrating structured exercise and lifestyle PA counselling within mental health and primary-care settings may enhance recovery, reduce cardiometabolic risk, and improve long-term prognosis.